Management of chronic pain in the elderly: focus on transdermal buprenorphine - Nalini Vadivelu (Dove Medical Press, 2008)
Nalini Vadivelu, Roberta L HinesDepartment of Anesthesiology, Yale University School of Medicine, New Haven, USAAbstract: Chronic pain in the elderly is a significant problem. Pharmacokinetic and metabolic changes associated with increased age makes the elderly vulnerable to side effects and overdosing associated with analgesic agents. Therefore the management of chronic cancer pain and chronic nonmalignant pain in this growing population is an ongoing challenge. New routes of administration have opened up new treatment options to meet this challenge. The transdermal buprenorphine matrix allows for slow release of buprenorphine and damage does not produce dose dumping. In addition the long-acting analgesic property and relative safety profile makes it a suitable choice for the treatment of chronic pain in the elderly. Its safe use in the presence of renal failure makes it an attractive choice for older individuals. Recent scientific studies have shown no evidence of a ceiling dose of analgesia in man but only a ceiling effect for respiratory depression, increasing its safety profile. It appears that transdermal buprenorphine can be used in clinical practice safely and efficaciously for treating chronic pain in the elderly.Keywords: transdermal buprenorphine, chronic pain, elderly